An adult choledochocele case presented with gastric outlet obstruction: A rare presentation - Mehmet Fatih CAN,; Nihat KAYMAKÇIOĞLU,; Gökhan YAĞCI,; Semih GÖRGÜLÜ,; Turgut TUFAN, (Turkish Journal of Gastroenterology, 2019)
-